The Urgency of Digital Literacy Based on Character Education in Learning Society 5.0 - Prihatmojo, Agung; Ruchiyat, Marina Gusnia; Marwan, Marwan; Badawi, Badawi; Kisworo, Tinto Wahyu (International Journal of Theory and Application in Elementary and Secondary School Education, 2024)
In the rapid development of technology, teachers in learning need to combine digital literacy and character to improve the quality of education. This article aims to determine the importance of digital literacy skills based on character education in a learning approach that integrates digital technology and prioritizes student character development in the 5.0 era. The research method used is a qualitative descriptive method with a literature review approach using various literature such as books, journals and scientific articles as the main object. The research results show that the application of digital literacy in the context of character education can improve students' ability to use technology and develop positive character in the era of society 5.0. Digital literacy-based character education strategies implemented by teachers are 1) watching educational content for 15 minutes at the beginning of the lesson via a digital platform (YouTube) with a critical attitude as an effort to solve problems, 2) the school recommends learning sites to students using laptop media and computers available in the school laboratory.